2017
DOI: 10.3390/en10070945
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of a 4 × 6 Oil-Free Twin-Screw Compressor

Abstract: The screw compressor in the early stage of development is generally known as the oil-injection type. However, escalating environmental problems and advances in electronic components have spurred continuous R & D to minimize the oil content in compressed air. The oil-free twin-screw compressor is continuously compressed by inner volumetric change between rotors and casing. Fo this reason, in order to predict the overall performance of the screw compressor at the early stage of the design process, industry still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…As a case, Wu et al [73,74] applied the TwinMesh to generate the rotor grid for a refrigeration TSC. Additionally, some common commercial software, such as Gambit [75] and STAR-CCM+ [76], can also be used to generate dynamic grids for twin-screw machines, but are hardly used owing to the inconvenience.…”
Section: Cfd Modelmentioning
confidence: 99%
“…As a case, Wu et al [73,74] applied the TwinMesh to generate the rotor grid for a refrigeration TSC. Additionally, some common commercial software, such as Gambit [75] and STAR-CCM+ [76], can also be used to generate dynamic grids for twin-screw machines, but are hardly used owing to the inconvenience.…”
Section: Cfd Modelmentioning
confidence: 99%
“…Byeon et al [15] used overlapping grid technology to simulate the working process of an oil-free air compressor. The experiment obtained the adiabatic efficiency and volumetric efficiency of the compressor where the simulation results were very similar to the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al [6] presented a CFD analysis of reciprocating refrigeration compressor, and numerical results demonstrated that compressor efficiency could be dramatically increased by improvement of the suction muffler and flow area of discharge valve. Byeon et al [7] applied a recently proposed overset grid method to the solution of the flow around a moving boundary. Kim et al [8] applied a 3D compressible Reynolds-averaged numerical model to examine the compressor flow and the acoustic behavior of a suction muffler.…”
Section: Introductionmentioning
confidence: 99%